2006
DOI: 10.1016/j.ejcts.2006.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Complete stable remission after extended transsternal thymectomy in myasthenia gravis☆

Abstract: Extended transsternal thymectomy is a good treatment tool to achieve CSR in MG. Thymomatous MG and non-thymomatous MG were significantly different in patient characteristics and prognosis. Prognostic factors were steroid therapy and age of onset in non-thymomatous MG, and steroid therapy in thymomatous MG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
2
25
0
2
Order By: Relevance
“…The prognosis of non-thymomatous patients seems to depend on age of onset and immunosuppressive therapy, whereas prognosis of thymomatous patients depends on immunosuppressive therapy only. 33 Thymectomy does not appear to impair the immune status of the majority of childhood patients, but it should be undertaken with caution in very young children due to the occurrence of some immunological abnormalities in this group postthymectomy.…”
mentioning
confidence: 94%
“…The prognosis of non-thymomatous patients seems to depend on age of onset and immunosuppressive therapy, whereas prognosis of thymomatous patients depends on immunosuppressive therapy only. 33 Thymectomy does not appear to impair the immune status of the majority of childhood patients, but it should be undertaken with caution in very young children due to the occurrence of some immunological abnormalities in this group postthymectomy.…”
mentioning
confidence: 94%
“…Despite few objections [4], a consensus on the efficiency and requirement for thymectomy prevails [5][6][7][8][9][10]. However, selection of the patients who would benefit most from thymectomy and the optimal operation method have been the focus of recent studies [8,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Currently extended transsternal thymectomy remains as the gold standard tool to achieve complete remission rates in MG [1,[3][4][5][6]. Late results demonstrated that complete remission rates were significantly better in extended transsternal thymectomies compared to basic transsternal thymectomies [8].…”
mentioning
confidence: 99%
“…The literature draw attention to patients with non-thymomatous MG obtaining significantly higher rates of complete stable remission than the patients with thymomatous MG [3][4][5]. The additional prognostic factors were stated as steroid therapy, age of onset, short duration of the disease and finally positive acetylcholine receptor antibodies [1,[4][5][6].The results of a recent survey of current surgical practice in thymic disease amongst EACTS members showed that, 80.8 % of the surgeons perform thymectomy for both MG and thymic cancer, 78.4% have a strict cooperation with dedicated neurologist and anesthesiologist during the course of treatment and 55.8% operate thymic hyperplasia with Stage I MG (ocular myasthenia) [7].Although there is no published information, in most of the clinics that I communicate during my surgical practice there has been a debate between neurologists and thoracic surgeons if surgery should be a part of MG treatment. Unfortunately the resistance of some neurologists to surgery for suitable patients was difficult to understand which might be due to obstacles to establish a multidisciplinary team.…”
mentioning
confidence: 99%
See 1 more Smart Citation